SLR : PENGARUH MEDIA SOSIAL DALAM MENINGKATKAN MINAT KUNJUNGAN WISATAWAN - Iqbal, Muhammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to explore the influence of social media on tourist interest in visiting using a Systematic Literature Review (SLR) approach. Through an analysis of 15 articles, it was found that social media has a positive influence ranging from 6.3% to 70.2% on tourist interest in visiting. Social media not only functions as a promotional tool but also shapes tourists' perceptions and expectations. The quality and consistency of content, as well as the selection of platforms such as Instagram and YouTube, are key factors in the effectiveness of promotions. However, challenges in social media management, such as limited resources and a lack of content strategy, still exist. This study recommends that destination managers enhance visual content and collaborate with influencers to maximize the positive impact on tourist visitation interest.Keywords: Social Media, Visitor Interest, Marketing Strategy, SLR.